In vitro organic control of Phytophthora cinnamomi with essential oils of oregano and clove - Ochoa Fuentes, Yisa María; Hernández Pérez, Anselmo; Delgado Ortiz, Juan Carlos; Cerna Chavez, Ernesto; Aguirre Uribe, Luis Alberto; Tapia-Vargas, Luis Mario (Revista Mexicana de Ciencias Agrícolas, 2019)
Michoacán is the leading avocado producing state in the world; however, root diseases decimate and damage the trees causing their death. The aim of the present investigation was to evaluate the organic control of the in vitro growth of Phytophthora cinnamomi with essential oils of oregano (Lippia berlandieri) and clove (Syzygium aromaticum). In the months of October and November 2016, root samples were collected from trees with symptoms of the disease in avocado (Persea americana Mill. Var. Hass), in the INIFAP experimental garden located in San Juan Nuevo Parangaricutiro, Michoacán. The isolates were identified morphologically and molecularly. The control of P. cinnamomi with essential oils of oregano and clove was evaluated determining the mean inhibitory concentration and its fiducial limits to 95% by means of a Probit regression by the method of maximum likelihood. The analyzes were carried out using the statistical program R 3.4. According to the results obtained, in relation to the inhibition of growth there is a reduction in the growth of P. cinnamomi. The essential oils of clove (Syzygium aromaticum) and oregano (Lippia berlandieri) are a natural alternative for the control of the oomycete P. cinnamomi for their fungicidal activity at low concentrations so they can be included in integrated disease management programs.